A Novel Ultrasound-Guided “Three in One” Approach Plus Interfascial Plane Blocks for the Treatment of Cervicogenic Headache - Ma D; Maimaitimin A; Wang Y (Local and Regional Anesthesia, 2024)
Danxu Ma,1 Abulaihaiti Maimaitimin,2 Yun Wang3 1Department of Anesthesiology and Pain Medicine, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Rheumatology and Immunology, Moyu Uighur Medicine Hospital, Xinjiang, People’s Republic of China; 3Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Yun Wang, Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, No. 95 Yongan Road, Xicheng District, Beijing, 100050, People’s Republic of China, Email wangyun129@ccmu.edu.cnObjective: Cervicogenic headache (CEH) is a condition resulting from upper cervical spine dysfunction and associated structural and soft tissue abnormalities, significantly impacting patients’ quality of life. To acquire better therapeutic results, we presented a novel ultrasound-guided “three in one” approach plus interfascial plane (IFP) blocks for the treatment of CEH. This approach allows for the modulation of C2 dorsal root ganglion (DRG), third occipital nerve (TON), and C3 medial branch with one-point puncture. Additionally, it allows for IFP blocks between the upper neck and occipital muscles within the same scanning plane.Patients and Methods: We evaluated patients diagnosed with CEH from July 2021 to December 2022 in our pain clinic. We included those who did not respond to conservative treatment and single occipital nerve block, therefore received nerve block or pulsed radiofrequency (PRF) using the “Three in One” approach plus IFP blocks. The accuracy of the ultrasound-guided C2 DRG puncture procedures was confirmed through fluoroscopy with C-arm and the sensory testing of PRF. The therapeutic effect of these interventions was assessed using the numerical rating scale (NRS) scores during telephone follow-ups at 1, 3, and 6 months.Results: Utilizing the “Three in One” approach, a total of 5 patients diagnosed with CEH underwent nerve block plus IFP blocks, while 2 patients underwent PRF plus IFP blocks. Employing ultrasound-guided C2 DRG puncture procedures, the needle tip’s correct placement was confirmed through both fluoroscopy and sensory testing of PRF. Notably, none of the cases experienced any complications associated with the approach. Subsequent follow-up assessments revealed an improvement in the NRS scores for CEH in all patients.Conclusion: The ultrasound-guided “Three in One” approach plus IFP blocks may be a potential effective method for the treatment of CEH.Keywords: cervicogenic headache, interfacial plane blocks, pulsed radiofrequency, C2 dorsal root ganglion, third occipital nerve